The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5664/jcsm.7482
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sleep Disturbances and Pain in Veterans With Comorbid Traumatic Brain Injury and Posttraumatic Stress Disorder

Abstract: Study Objectives: Veterans are at an increased risk for traumatic brain injury (TBI) and posttraumatic stress disorder (PTSD), both of which are associated with sleep disturbances and increased pain. Furthermore, sleep disturbances and pain are reciprocally related such that each can exacerbate the other. Although both TBI and PTSD are independently linked to sleep disturbances and pain, it remains unclear whether Veterans with comorbid TBI+PTSD show worse sleep disturbances and pain compared to those with onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 99 publications
4
35
0
Order By: Relevance
“…One study assessed 12 different symptoms in physical, cognitive, and emotional categories, and found that noise sensitivity and anxiety were the only two initial TBI symptoms that were significant predictors for persistent post concussive syndrome 66 . Furthermore, another study showed that patients with chronic TBI showed persistent auditory sensitivity in a subset patients that were comorbid with PTSD 67 . Additional recent work by Papesh et al .…”
Section: Discussionmentioning
confidence: 99%
“…One study assessed 12 different symptoms in physical, cognitive, and emotional categories, and found that noise sensitivity and anxiety were the only two initial TBI symptoms that were significant predictors for persistent post concussive syndrome 66 . Furthermore, another study showed that patients with chronic TBI showed persistent auditory sensitivity in a subset patients that were comorbid with PTSD 67 . Additional recent work by Papesh et al .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 TBI likely changes the brain's ability to appropriately control breathing during sleep and affect circadian rhythms via hormonal channels such that the internal "clock" in the brain may become disoriented. In turn, sleep disturbance complicates the resolution of TBI symptoms 25 and contributes to irritability, cognitive impairment, memory loss, impulsivity, poor concentration, depression, and even hallucinations and paranoia. 26,27 Moreover, the physical and medical effects on the human body are also profound.…”
Section: Sleep Disturbancementioning
confidence: 99%
“…Certainly, there are many potential factors contributing to PVT failures. Iraq and Afghanistan Veterans frequently present with high levels of psychiatric distress, sleep disturbances, chronic pain, and other psychosocial stressors (Balba et al, 2018;Hoge et al, 2008;Seal et al, 2016;Stojanovic et al, 2016) that can greatly impact engagement in the assessment process and contribute to PVT failure (Jak et al, 2015;Lange, Pancholi, Bhagwat, Anderson-Barnes, & French, 2012). Thus, when neuropsychologists encounter PVT failure in a clinical context, a referral for psychotherapy may be made to address underlying factors such as mental health symptoms that could be contributing to a patient's distress and/or PVT failure (Carone et al, 2010).…”
mentioning
confidence: 99%